Kontaminasi Senyawa Polisiklik Aromatik Hidrokarbon (PAH) dalam Sedimen Di DAS Gending, Probolinggo - Edward Edward (Depik, 2018)
Polycyclic aromatic hydrocarbons are very toxic and persistent environmental contaminants. This study were carried out in Gending watershed Probolinggo in March 2014, the propose of this research was to known  the concentrations and possible sources of 16 PAHs (Polycyclic aromatic hydrocarbons) classified by the United State Environmental Protection Agency as priority pollutants.   Sediment samples were taken by using a sediment sampler at 6 research stations. The concentration of PAH were determined  using Gas Chromatography-Mass Spectrometry (GC-MS)  and the sources using individual ratio diagnose method. The results show that  the concentration of PAHs in  sediment still low and fixed with the safe threshold values for waters organisms. Individual PAH dominated by high molecule weight PAHs. The results of PAHs ratio individual analysis showed that PAHs sources in sediment derived from a variety of sources such as; oil spill, oil combustion and combustion of organic materials. To reduce the level of PAHs pollution in sediment in Gending watersheds need to make efficiency in using of fossil fuel, reduce oil spill and  combustion of oil and organic materials and implementing of laws and sanctions against polluters.